2008
DOI: 10.3844/jmssp.2008.161.167
|View full text |Cite
|
Sign up to set email alerts
|

Solving the Vehicle Routing Problem with Stochastic Demands via Hybrid Genetic Algorithm-Tabu Search

Abstract: This study considers a version of the stochastic vehicle routing problem where customer demands are random variables with known probability distribution. A new scheme based on a hybrid GA and Tabu Search heuristic is proposed for this problem under a priori approach with preventive restocking. The relative performance of the proposed HGATS is compared to each GA and TS alone, on a set of randomly generated problems following some discrete probability distributions. The problem data are inspired by real case of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 19 publications
0
13
0
2
Order By: Relevance
“…Both algorithms are categorized as Ant Colony Optimization (ACO) algorithms. In particular, it can be observed that ACS is the most aggressive of the ACO algorithms and it returns the best solution quality for very short computation times [5,7] . ACS has an advantage over Simulated Annealing and Genetic Algorithm approaches when the graph may change dynamically where the Ant Colony algorithm can be run continuously and adapt to changes in real time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both algorithms are categorized as Ant Colony Optimization (ACO) algorithms. In particular, it can be observed that ACS is the most aggressive of the ACO algorithms and it returns the best solution quality for very short computation times [5,7] . ACS has an advantage over Simulated Annealing and Genetic Algorithm approaches when the graph may change dynamically where the Ant Colony algorithm can be run continuously and adapt to changes in real time.…”
Section: Discussionmentioning
confidence: 99%
“…The problem described above can be modeled as a Vehicle Routing Problem with Stochastic Demand (VRPSD) as the amount of solid waste is stochastic and may be presented in a complete graph [7] and Secomandi, [9,10] . Let the set of nodes be {0, 1,…,n}.…”
Section: Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar case study could be seen in Irhamah and Ismail (2009) and Ismail and Irhamah (2008). This research tries to refine CARP model with stochastic demand (CARPSD) and CARP with time windows (CARPTW) according to specific case of truck operation in waste collection by taking into account the element of rain drops.…”
Section: Problem Identificationmentioning
confidence: 99%
“…Many researches' have been done in VRP using GA (Ismail and Irhamah, 2008). proposed a new scheme based on a hybrid GA and Tabu Search heuristic for VRPSD with preventive restocking.…”
Section: Heuristic Algorithm For Vrpsdmentioning
confidence: 99%